FUNGSI MELAYANI KEPENTINGAN SOSIAL DALAM REFORMASI HUKUM MENUJU HUKUM RESPONSIF - Soenyono Soenyono (Lembaga Penelitian Universitas YARSI, 2019)
Laws, according to Philippe Nonet and Philip Selznick, have fallen into three categories:repressive, autonomy, and responsive laws. Responsive law particularly deals with publicservice. This research prioritizes literature study on the theories of law by Nonet-Selznick,supported by juridical studies on legislation which is in line with responsive law. Thefindings of this research suggest that law can perform–in this regard, to serve the publicinterest—well on several conditions: (1) its substance highly values public interest andsocial justice, (2) it is implemented by sound and reliable legal institutions supported byhigh-integrity apparatus, (3) people consciously abide by the law. Therefore, achieving theexistence of the so-called responsive law—that is the law which provides the people withprotection and serves the public interests based on legal, moral, and social justice—requires (1) the development of law substances to uphold social interest and social justice,(2) the establishment of a legal institution which is responsive to social needs and publicdynamics, and (3) the promotion of legal awareness.